Política fiscal e os ciclos econômicos - Daniel, Flávio Portella (2008)
This paper is aimed to show the relation between fiscal policy and business cycles using the structural budget balance as a tool to define the cyclical part of the fiscal results. We believe the better use of fiscal policy should respect business cycles because a pattern of economic growth today may not be seen in the future. This fact may cause a direct impact to the welfare state. Thus, we did a review of literature where we could see that the better fiscal action before business cycles is a counter-cyclical fiscal policy. However, this policy has been in use for just developing countries. Volatility of the government spending, access to international market credit, political pressures, control of corruption and level of fiscal institutions can limit the application of optimal fiscal policy during the business cycles